A study on public employees’ perception towards the implementation of new retirement policy in Malaysia / Nadhirah Shamsulkamar and Nurashikim Yunoh - Shamsulkamar, Nadhirah; Yunoh, Nurashikim (Faculty of Administrative Science and Policy Studies, 2012)
The ageing workforce has created a number of issues, one of which is the increased interest in, and importance of, the retirement of older workers. Governments are encouraging older workers to continue working later in life, and to delay their retirement to offset the dependence on the support of (the fewer) younger workers by increased the age of retirement from 58 to 60 years. This paper aims to look at the association between the public employees’ perception towards the implementation of new retirement policy. This study involves 91 public sectors employees from various organization such as from Malaysia Department of Insolvency (MdI) Temerloh, Pahang, UiTM Campus Bandaraya Melaka, Sekolah Kebangsaan Tedong, Merlimau Melaka, Jabatan Perangkaan Malaysia Negeri, Melaka, Kementerian Dalam Negeri, Melaka, Jabatan Kesihatan Negeri Melaka, Kementerian Kewangan Negeri Melaka, and the last is Pejabat Perdagangan Dalam Negeri, Koperasi, dan Kepenggunaan Melaka as our respondents using questionnaire. Our objectives are (1) we want to determine whether there is relationship between new retirement policy with job performance, financial security, job satisfaction, and quality of life, (2) What is the level of perception among the public sector employees towards the implementation of new retirement policy in terms of four variables such job performance, financial security, job satisfaction and quality of life, (3) The factors that most influence the public employees perception towards the implementation of new retirement policy. The findings show that there are negative relationship between the new retirement policy with the job performance, financial security, job satisfaction and quality of life. Job performance, financial security, job satisfaction and quality of life shows a negligible relationship with the value of -.547-.337, -.475 and -.308 respectively. The factor that most influence the public employees’ perception towards the implementation of new retirement policy is job performance. We also found out that the percentage of civil servants that agree to the new retirement policy is 59.3% while only 40.7% of civil servants were disagree about this policy. From this situation we can concluded that the majority of civil servant agree with the new retirement policy.